A Comparison Study of Olmesartan and Valsartan Effects on Myocardial Metabolism in Patients With Dilated Cardiomyopathy: the OVOID Trial - Sangyong Jo; Kyungil Park; Jae Hyuk Choi; Chang‐Bae Sohn; Jeonghwan Kim; Yong‐Seop Kwon; Su Hong Kim; Tae‐ho Park (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Myocardial metabolism plays an important role in maintaining cardiac function. Patients with dilated cardiomyopathy exhibit alterations in myocardial metabolism characterized by increased myocardial glucose metabolism. This study aimed to evaluate effects on myocardial metabolism of the angiotensin II receptor blockers olmesartan and valsartan in patients with dilated cardiomyopathy. We hypothesized that olmesartan, owing to its stronger and longer‐lasting angiotensin II receptor blockade, would lead to a greater reduction in myocardial glucose metabolism compared with valsartan. Methods OVOID (A Comparison Study of Olmesartan and Valsartan Effects on Myocardial Metabolism in Patients With Dilated Cardiomyopathy) was a multicenter, randomized controlled trial involving 44 patients with New York Heart Association classes II through IV dilated cardiomyopathy. Participants were randomized 1:1 to receive olmesartan (20 mg once daily) or valsartan (160 mg twice daily) for 6 months, in addition to standard care. The primary outcome was myocardial glucose metabolism measured by standardized uptake value ratio at 6 months after treatment. To measure standardized uptake value ratio, 18F‐fluoro‐2‐deoxyglucose cardiac positron emission tomography was performed at baseline and 6 months after receiving the study agent. Results Baseline clinical characteristics and standardized uptake value ratio were not significantly different between the 2 groups. The average left ventricular ejection fraction was 25.1%±7.8% at baseline, with significant improvement in both groups after 6 months, though with no difference between them. At 6 months, the standardized uptake value ratio value was significantly lower in the olmesartan group than that in the valsartan (3.76±2.00 versus 5.76±3.10; P=0.01). Conclusions Six months of olmesartan therapy significantly decreased myocardial glucose metabolism in dilated cardiomyopathy patients compared with valsartan therapy for 6 months. Registration URL: https://www.clinicaltrials.gov; Unique identifier: NCT04174456.